The human liver‐specific proteome defined by transcriptomics and antibody‐based profiling. Issue 7 (19th March 2014) - Kampf, Caroline; Mardinoglu, Adil; Fagerberg, Linn; Hallström, Björn M.; Edlund, Karolina; Lundberg, Emma; Pontén, Fredrik; Nielsen, Jens; Uhlen, Mathias
ABSTRACT: Human liver physiology and the genetic etiology of the liver diseases can potentially be elucidated through the identification of proteins with enriched expression in the liver. Here, we combined data from RNA sequencing (RNA‐Seq) and antibody‐based immunohistochemistry across all major human tissues to explore the human liver proteome with enriched expression, as well as the cell type‐enriched expression in hepatocyte and bile duct cells. We identified in total 477 protein‐coding genes with elevated expression in the liver: 179 genes have higher expression as compared to all the other analyzed tissues; 164 genes have elevated transcript levels in the liver shared with at least one other tissue type; and an additional 134 genes have a mild level of increased expression in the liver. We identified the precise localization of these proteins through antibody‐based protein profiling and the subcellular localization of these proteins through immunofluorescent‐based profiling. We also identified the biological processes and metabolic functions associated with these proteins, investigated their contribution in the occurrence of liver diseases, and identified potential targets for their treatment. Our study demonstrates the use of RNA‐Seq and antibody‐based immunohistochemistry for characterizing the human liver proteome, as well as the use of tissue‐specific proteins in identification of novel drug targets and discovery of biomarkers.—Kampf, C., Mardinoglu, A., Fagerberg, L., Hallström, B. M., Edlund, K., Lundberg, E., Pontén, F., Nielsen, J., Uhlen, M. The human liver‐specific proteome defined by transcriptomics and antibody‐based profiling. FASEB J . 28, 2901–2914 (2014). www.fasebj.org